2020
DOI: 10.5194/se-2020-25
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From subduction to collision in the Parautochthon and autochthon of the NW Variscan Iberian Massif

Abstract: A stacking of nappes forms the Parautochthonous Domain located beneath the Allochthonous Complexes of the NW Iberian Massif. Lower Paleozoic metasedimentary and felsic metavolcanic rocks, including some riebeckite gneiss, form the uppermost nappe of the Parautochthon. Micaschists of this nappe may contain albite porphyroblasts with aligned mineral microinclusions defining a relic internal schistosity. Thermobarometric estimates on the relic mineral assemblage 15 suggest an early M1 stage of High-Pressure, Low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Another possibility is that top-to-the-S and top-to-the-N could be conjugate movements of our E1 stage, as proposed for the Redondela-Beariz Detachment in Díez Fernández et al (2012b), and for Bande-Celanova Dome in this manuscript. This one is a more likely option, as top-to-the-south (sinistral) shearing in the eastern limb affects the Beariz granite as well (González Cuadra et al, 2006). Topto-the-north kinematic criteria are also found by Gloaguen et al, 2014 (and references therein) to the east of Forcarei, where the authors relate both, stretching lineations (our E1) and upright folds (our C3), with a post-D2 (main thrusting) stage D3.…”
Section: Interactive Commentmentioning
confidence: 99%
“…Another possibility is that top-to-the-S and top-to-the-N could be conjugate movements of our E1 stage, as proposed for the Redondela-Beariz Detachment in Díez Fernández et al (2012b), and for Bande-Celanova Dome in this manuscript. This one is a more likely option, as top-to-the-south (sinistral) shearing in the eastern limb affects the Beariz granite as well (González Cuadra et al, 2006). Topto-the-north kinematic criteria are also found by Gloaguen et al, 2014 (and references therein) to the east of Forcarei, where the authors relate both, stretching lineations (our E1) and upright folds (our C3), with a post-D2 (main thrusting) stage D3.…”
Section: Interactive Commentmentioning
confidence: 99%
“…The works by Dias da Silva et al in the eastern area of Morais concluded that most of the previously considered Lower Allochthon (e.g. Ribeiro et al, 2006) is currently a part of the parautochthonous section. The lawsonite-bearing rocks (HP) described in that area by Schermerhörn and Kotsch (1984) -and cited in their work-, were then interpreted as belonging to a possible, thin, uppermost unit of the top of the Parautochthon (please see Fig.…”
Section: Sectionmentioning
confidence: 99%